1994
DOI: 10.1063/1.870664
|View full text |Cite
|
Sign up to set email alerts
|

Ignition and high gain with ultrapowerful lasers*

Abstract: Ultrahigh intensity lasers can potentially be used in conjunction with conventional fusion lasers to ignite inertial confinement fusion (ICF) capsules with a total energy of a few tens of kilojoules of laser light, and can possibly lead to high gain with as little as 100 kJ. A scheme is proposed with three phases. First, a capsule is imploded as in the conventional approach to inertial fusion to assemble a high-density fuel configuration. Second, a hole is bored through the capsule corona composed of ablated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
1,655
0
11

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,928 publications
(1,674 citation statements)
references
References 21 publications
8
1,655
0
11
Order By: Relevance
“…However, in the presence of an inhomogeneity an additional drift velocity V n = B × ∇n/n 2 for the structure exists. This can be observed by substituting for g from equation (2) to equation (1). Here B is the magnetic field associated with the structure.…”
Section: Theoretical Mechanism For Hot Electron Stopping Through a Dementioning
confidence: 99%
See 1 more Smart Citation
“…However, in the presence of an inhomogeneity an additional drift velocity V n = B × ∇n/n 2 for the structure exists. This can be observed by substituting for g from equation (2) to equation (1). Here B is the magnetic field associated with the structure.…”
Section: Theoretical Mechanism For Hot Electron Stopping Through a Dementioning
confidence: 99%
“…Efforts to realize laser fusion received a major boost with the fast ignition proposal in 1994 [1]. This proposal seeks to implode/compress a fusion pellet by multiple, high-energy, nanosecond laser pulses and then strike a spark in the compressed core at the time of maximum compression.…”
Section: Introductionmentioning
confidence: 99%
“…These self-generated (or externally applied) transverse and axial magnetic fields affect the propagation of laser pulses in plasmas since the canonical momentum in a magnetized plasma is not conserved [6,7]. Furthermore, laser pulse interaction with magnetized plasmas finds various applications for different branches such as: nonlinear interaction [8], wakefield excitation [9], modulation instability [10,11], laser fusion schemas [12,13], and fast ignition schemes in inertial confinement fusion (ICF) [14]. Moreover, self-generated magnetic fields in the corona region have been studied for intense laser pulse interaction with magnetized plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the product of B / L / needs to be larger than the fast electron momentum to reflect the fast electrons back towards the guide axis. The resistive guide has been suggested for applications such as the Fast Ignition approach to the inertial confinement fusion scheme 6,7 where the energetic fast electrons need to be guided through an overdense stand-off distance of 100 lm or more 8 and deposited into the compressed core of deuterium-tritium (DT) plasma. It has been suggested that a resistive guide element can also be used as a driver in hydrodynamic experiments 4,9 since strong heating occurs where the fast electron beam is collimated.…”
Section: Introductionmentioning
confidence: 99%